PERFORMANCE EVALUATION OF ACTIVATED CARBON PRODUCED FROM CORNCOB, COW BONE, AND COCONUT SHELL AS A FILTER MEDIUM (FUDMA JOURNAL OF SCIENCES, 2024)
Inaccessibility of safe drinking water coupled with poor sanitation and hygiene and its attendance effect is estimated to cost Nigeria about 1.3 billion dollars. The rural communities adopted different methods to filter their water however these methods have proven ineffective in removing certain impurities. The use of fabric cannot remove the microorganisms and chemicals present in water. It is given that activated carbon filters are applied in the removal of these chemicals to test the performance of activated carbon made from corncob, cow bone, and coconut shell as a filter medium, activated carbons were used separately, and combined in a model filter. Raw water samples from Kubanni River and the borehole in 55 apartment Dogon Itche Samaru, Zaria were filtered by the model without pretreatment. The sieve analysis carried out on the activated corncob, cow bone, and coconut shell shows effective sizes of 0.27mm, 0.08mm, and 0.21mm; and uniformity coefficients of 2.11, 5.38, and 2.33 respectively. The analysis showed that the combined media has the highest turbidity removal, 92% for the river sample and 89% for the borehole sample. In terms of acidity and chloride removal, the activated corncob gave better filtrate quality: 19% and 13% removal respectively. In the case of alkalinity, the activated cow bone and coconut shell showed a gradual removal in alkalinity from the borehole sample. The combined media showed more tendency to remove hardness compared to the other activated carbons
Keywords: Activated carbon; Effective size; Uniformity coefficient; Turbidity removal; Hardness; Filter medium